Outcome of anorexia nervosa in males. - Burns, T; Crisp, A (1984)
Twenty-seven consecutive male patients suffering from anorexia nervosa were followed-up 2-20 years after presentation; 20 had been treated with an in-patient refeeding/psychotherapy regime. The outcome of the series compared very closely with a similar group of female anorectics: 12 (44%) had a good outcome, stable weight restoration and normal sexual functioning; seven (26%) had an intermediate outcome, and eight (30%) poor (weight more than 15% below normal, and poor or no sexual activity). No patient had died. Good outcome in terms of weight was associated with good psychological and social functioning, while poor outcome was clearly associated with a longer duration of illness, previous treatment, and greater weight-loss during illness, although not with any specific dietary behaviour. Poor relationship with parents during childhood and the absence of normal adolescent sexual behaviour premorbidly were also strongly predictive of poor outcome.